2019
DOI: 10.24898/tandro.2019.87360
|View full text |Cite
|
Sign up to set email alerts
|

Farklı kültürlerde jinekolojik ve meme kanserli kadın hastaların seksüaliteye bakış açıları ve yaşadıkları sorunlar

Abstract: İnsan sosyolojik, psikolojik, kültürel ve fizyolojik yönleriyle, birçok alt sistem ve yapıdan oluşan bütünleşik ve kompleks bir varlık olup değişen ve gelişen zaman içerisinde çevresel etkileşim dinamizmi altında, her geçen gün farklılaşmakta ve sahip olduğu bu biyo-psiko-sosyal yapısının devamlılığını sağlamaktadır. [1] Bu yaşam döngüsü içerisinde bireyin sosyokültürel olarak sağlık kavramına bakış açısı değişmekte ve kaliteli yaşam kavramı öne çıkmaktadır. Dolayısıyla kaliteli yaşamı olumsuz yönde etkileyen,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…In previous studies, sexually active women experienced a decrease (41.0%-53.0%) in sexual interest in posttreatment month 3 and in sexual activity and sexual satisfaction in posttreatment months 6 and 12 compared with the pretreatment period 11,21,22 . Similar findings from previous studies indicated perceptions of impaired sexual function and resulting anxiety in 54.0% to 70.5% of study participants 12,23 . Additional reported experiences include communication problems between spouses, anxiety of not being liked by the spouse, fear of infecting/getting infected by the spouse, the belief that sexuality harms the wife, and sexual conflicts, which decrease sexual satisfaction and marital satisfaction 8,23 .…”
Section: Discussionsupporting
confidence: 70%
See 4 more Smart Citations
“…In previous studies, sexually active women experienced a decrease (41.0%-53.0%) in sexual interest in posttreatment month 3 and in sexual activity and sexual satisfaction in posttreatment months 6 and 12 compared with the pretreatment period 11,21,22 . Similar findings from previous studies indicated perceptions of impaired sexual function and resulting anxiety in 54.0% to 70.5% of study participants 12,23 . Additional reported experiences include communication problems between spouses, anxiety of not being liked by the spouse, fear of infecting/getting infected by the spouse, the belief that sexuality harms the wife, and sexual conflicts, which decrease sexual satisfaction and marital satisfaction 8,23 .…”
Section: Discussionsupporting
confidence: 70%
“…11,21,22 Similar findings from previous studies indicated perceptions of impaired sexual function and resulting anxiety in 54.0% to 70.5% of study participants. 12,23 Additional reported experiences include communication problems between spouses, anxiety of not being liked by the spouse, fear of infecting/ getting infected by the spouse, the belief that sexuality harms the wife, and sexual conflicts, which decrease sexual satisfaction and marital satisfaction. 8,23 These sexual and psychosocial problems experienced by couples threaten the emotional and physical contact between them and negatively affect their sexual satisfaction.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations